STRATEGIES TO IMPROVE THE ACADEMIC QUALIFICATIONS OF EDUCATORS AT THE AL FALAH FOUNDATION - Indah Yulie Rahmawati; Muhammad Munadi; Indah Nurhidayati (Profetika: Jurnal Studi Islam, 2024)
This study aims to find out: 1) What is the Strategy for Improving the Academic Qualifications of Educators at the Al Falah Foundation for the 2023/2024 Academic Year? 2) What are the supporting and inhibiting factors in the implementation of the Educator Academic Qualification Improvement Strategy at the Al Falah Foundation for the 2023/2024 Academic Year? This study uses descriptive qualitative research. The research was conducted at the Al Falah Foundation. The subject of this research is the Chairman of the Foundation. The informants are members of the Foundation, teachers, and committees. Data collection was carried out by observation, interview, and documentation methods. The results of the study show that: 1) The strategy used by the Al Falah Foundation is to encourage teachers to continue higher education such as providing subsidies for teachers who continue their S2, in addition to including educators to be active in workshops/seminars and training to provide skills and provide rewards for creative, innovative educators in carrying out the learning process, 2) Every organization or institution will experience challenges or supporting elements,  including the Al Falah Foundation, which at the Al Falah Foundation is supported by the Foundation's ease of allowing teachers to advance their studies, the existence of In House Training (IHT) activities at the beginning of each school year which aims to train educators to improve the performance of their teachers, and the existence of an agenda for school principals to supervise their educators.